Unveiling the key factors and challenges on the graduates’ board performance in the new curriculum - Panlaqui, Catheryn (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
This study explores the essential factors and challenges shaping the Board Licensure Examination for Professional Teachers (BLEPT) performance of Bachelor of Elementary Education graduates of Batch 2022 within the new curriculum framework. It intended to profile, describe the influencing factors on exam performance in terms of personal, school, and home-related/family factors, discover the challenges perceived to impact performance, and propose a sustainability plan to achieve better performance in the licensure exam. A mixed-method approach, specifically descriptive phenomenology was employed with 51 respondents in the quantitative and 14 participants in the qualitative part. Key findings show the dominance of females (82%) in teacher education, most of them attended the formal review sessions (75%), and the majority are passers (82%). Influences of factors have a very great extent which underscores positive self-perception in personal factors (4.36), satisfaction with school infrastructure, faculty competence, curriculum, and administration (4.57), and a generally supportive family environment, although with variations in parental monitoring (4.28). The challenges include work-life integration, financial strain, and psychological and emotional stress emphasizing the multifaceted nature of exam preparation. No significant disparities emerged based on sex and BLEPT outcome (student/personal factors, p = .249; school-related factors, p = .664; and home/family-related factors, p = .855), highlighting consistent influences across diverse groups. However, significant distinctions were discovered in student and home-related factors between formal review attendees and non-attendees (with Cohen’s d values of 0 .69 (large effect) and 0 .65 (large effect), respectively), emphasizing the impactful role of formal reviews. The study recommends a sustainability action plan to lessen these challenges and enhance the preparation process for future exam takers.